The Relationship Between the Availability of Digital Facilities and the Intensity of Technology Use with Elementary School Students' Readiness to Support the Smart City Concept through Technology-Based Learning - Celine Widyaningrum Kusumawardani; Agung Hastomo (FKIP - Universitas Riau, 2026)
Elementary school students’ readiness to meet the demands of a smart city remains relatively low, indicating a gap between technological advancement and students’ ability to utilize digital tools effectively. This study aims to examine the relationship between the availability of digital facilities and the intensity of technology use with students’ readiness to support the smart city concept through technology-based learning. This study employed a quantitative correlational approach with a sample of 428 fifth-grade students in Balikpapan. The results show that digital facilities availability has a positive and significant relationship with student readiness (r = 0.578; R² = 0.334; p < 0.001), while the intensity of technology use demonstrates a stronger positive and significant relationship (r = 0.712; R² = 0.507; p < 0.001). Simultaneously, both variables significantly contribute to student readiness (R = 0.742; R² = 0.551; p < 0.001). These findings highlight that improving not only access to digital facilities but also the quality and intensity of technology use is essential to strengthen students’ readiness in supporting smart city-based education.